Characteristics, prognosis, and treatment response in HFpEF patients with high vs. normal ejection fraction - Gu, Jun; Ke, Jia-han; Wang, Yue; Wang, Chang-qian; Zhang, Jun-feng (Frontiers in Cardiovascular Medicine, 2022)
Background Heart failure with preserved ejection fraction (HFpEF) patients varied by left ventricular ejection fraction (LVEF) have different clinical characteristics, prognosis, and treatment response. With data from our prospective HFpEF cohort, we assessed the possible relationship between clinical characteristics, outcome as well as treatment response and LVEF. Methods We compared differences in baseline characteristics and clinical outcomes across LVEF categories (50%≤LVEF <60% vs. LVEF≥60%) in 1,502 HFpEF patients, and determined whether LVEF modified the treatment response. During 5-year follow-up, all-cause mortality was used as the primary endpoints, and composite endpoints (all-cause mortality or HF hospitalization) were set as the secondary endpoint. Results Patients with higher LVEF were statistically older, more likely to be women and have a history of atrial fibrillation. Patients with lower LVEF category were more likely to have a history of coronary artery disease. The incidences of all-cause mortality and composite endpoints were higher in patients with higher LVEF. Also, LVEF modified the spironolactone treatment effect for the primary outcome and secondary endpoint with stronger estimated benefits at the lower LVEF category with respect to all-cause mortality (HR 0.734, 95% CI 0.541–0.997, P = 0.048) and all-cause mortality or HF hospitalization (HR 0.767, 95% CI 0.604–0.972, P = 0.029). Conclusion The characteristics and outcomes of HFpEF patients varied substantially by LVEF. Patients with higher LVEF encountered more adverse events than those with lower LVEF. The potential efficacy of spironolactone was greatest at the lower category of LVEF spectrum in HFpEF.